2014
DOI: 10.1155/2014/592986
|View full text |Cite
|
Sign up to set email alerts
|

Rattus norvegicus(Rodentia: Muridae) Infected byLeishmania(Leishmania)infantum(syn.Le. chagasi) in Brazil

Abstract: In the present study we surveyed the fauna of phlebotomine sand flies and small mammals in peridomestic areas from a Brazilian municipality where the American cutaneous leishmaniasis (ACL) is endemic. A total of 608 female phlebotomine sand flies were captured during nine months in 2009 and 2010. Seven different species were represented with 60% of them being Lutzomyia intermedia and Lu. whitmani, both incriminated vectors of ACL. Lu. longipalpis, a proven vector of visceral leishmaniasis (VL) was also capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
5
Order By: Relevance
“…Many rodent species, both in the Old World and the New World, have been suggested as possible reservoir hosts for various Leishmania species . In southern European countries, the investigation of involvement of wild rodents in the maintenance of Leishmania in nature is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many rodent species, both in the Old World and the New World, have been suggested as possible reservoir hosts for various Leishmania species . In southern European countries, the investigation of involvement of wild rodents in the maintenance of Leishmania in nature is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no obvious signs of disease, a fact that could contribute to the role of reservoir of these animals. Consequently, and as these rodents have an average life expectancy between 12 ( M. musculus ) and 24 months ( R. rattus and R. norvegicus ), it may be concluded that they live long enough to maintain the parasite available for a sufficient period of time .…”
Section: Discussionmentioning
confidence: 99%
“…At distances of 25-100 m between residences and in areas with forests and streams, important risk factors for human cases and canine leishmaniasis exist and offer greater contact with vectors and wild reservoirs of the parasite (Membrive et al, 2012). The invasion of humans and dogs in forest areas and the presence of rodents and synanthropic animals in peri-domestic environments are the main forms of contact with the LTCan parasite (Alvar et al, 2004;Dantas-Torres, 2007;Lara-Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…O ciclo biológico do Lutzomyia sp. se inicia com a deposição dos ovos em locais úmidos, ricos em matéria orgânica e de pouca luminosidade, não havendo fase evolutiva na água (1)(2)(3) . Nas Américas, as leishmanioses apresentam duas principais categorias clínicas, associadas a uma gama de sintomas e graus diferentes de severidade: Leishmaniose Visceral (LV) e a Leishmaniose Tegumentar Americana (LTA).…”
Section: Introductionunclassified